C−N Bond Formation from a Masked High‐Valent Copper Complex Stabilized by Redox Non‐Innocent Ligands. Issue 36 (9th August 2016) - Jacquet, Jérémy; Chaumont, Pauline; Gontard, Geoffrey; Orio, Maylis; Vezin, Hervé; Blanchard, Sébastien; Desage‐El Murr, Marine; Fensterbank, Louis
Abstract: The reactivity of a stable copper(II) complex bearing fully oxidized iminobenzoquinone redox ligands towards nucleophiles is described. In sharp contrast with its genuine low‐valent counterpart bearing reduced ligands, this complex performs high‐yielding C−N bond formations. Mechanistic studies suggest that this behavior could stem from a mechanism akin to reductive elimination occurring at the metal center but facilitated by the ligand: it is proposed that a masked high oxidation state of the metal can be stabilized as a lower copper(II) oxidation state by the redox ligands without forfeiting its ability to behave as a high‐valent copper(III) center. These observations are substantiated by a combination of advanced EPR spectroscopy techniques with DFT studies. This work sheds light on the potential of redox ligands as promoters of unusual reactivities at metal centers and illustrates the concept of masked high‐valent metallic species. Abstract : Cu III in hiding : A stable copper(II) complex bearing fully oxidized iminobenzoquinone redox ligands reacts as a copper(III) species and performs high‐yielding C−N bond formation. Mechanistic studies suggest that this behavior could stem from a mechanism akin to reductive elimination occurring at the metal center but facilitated by the ligand.